Competitive Strategies For Enhancing Soft Skills In Higher Education: Lessons From A Global Pandemic - Azlyn Ahmad Zawawi; Altamies Irfan Mazlan; Nur Mastura Mustafa Kamal (Advances in Humanities and Contemporary Studies, 2023)
The COVID-19 pandemic has had a significant impact on the labor market, increasing the importance of soft employability skills. Higher education institutions have had to adapt to produce graduates with the necessary competencies, especially in the shift towards remote work and virtual communication. This paper investigates the factors that influence the enhancement of soft skills among undergraduate students in a selected university in South Malaysia. 121 students participated in the study using a purposive sampling method and an online questionnaire as the data collection tool. The findings suggest a positive relationship between students’ awareness and the enhancement of soft skills, as well as significant relationships between university support, teaching methods, and soft skills enhancement. The study highlights the importance of early exposure to soft skills for better interpersonal relationships, effective decision-making, improved communication skills, and positive professional development. Therefore, universities need to emphasize developing students’ soft skills through comprehensive approaches that incorporate soft skills into the curriculum.